2018
DOI: 10.1002/fuce.201700218
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Behavior of Electrosprayed Carbon Black‐Nafion Composite Layers

Abstract: Electrosprayed composite films prepared from carbon and Nafion are especially suitable to be applied as microporous layers and protective coatings for a number of for proton exchange membrane fuel cell (PEMFC) components, due to of their particular properties. The electrospray deposition of carbon inks is a complex process that requires further study. In order to gain insight into the factors influencing the characteristics of electrosprayed films, the effect of some parameters has been analyzed. The solvent n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…For instance, Nafion is used to block out the anionic (negatively charged) ascorbate and accumulate the cationic (positively charged) dopamine in sensing electrodes. In the same system, the accumulation (trapping) effect of the Nafion and the subsequent signal enhancement have also been demonstrated. Furthermore, in the AB and Nafion IPA solution, aggregates between AB and Nafion are formed with sulfonic groups heading toward AB, as stated by Conde and Chaparro . This would finally result in AB aggregates covered by negatively charged hydrophobic chains.…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…For instance, Nafion is used to block out the anionic (negatively charged) ascorbate and accumulate the cationic (positively charged) dopamine in sensing electrodes. In the same system, the accumulation (trapping) effect of the Nafion and the subsequent signal enhancement have also been demonstrated. Furthermore, in the AB and Nafion IPA solution, aggregates between AB and Nafion are formed with sulfonic groups heading toward AB, as stated by Conde and Chaparro . This would finally result in AB aggregates covered by negatively charged hydrophobic chains.…”
Section: Resultsmentioning
confidence: 78%
“…Thus, the C 1s peak was deconvoluted into nine peaks corresponding to the functional groups C�C (sp 2 , 284.42 eV), C−C (sp 3 , 284.80), C−OH (sp 3 , 286.25 eV), C�O (sp 2 , 288.28 eV), and π−π*transition (290.7 eV), plus the binding energies corresponding to C−F bonds, namely, -OCF 2 (289.50 eV), −CF 2 (291.95 eV), and −CF 3 (293.62 eV), in good agreement with previously reported binding energies. 27 In Figure S4, the O 1s peak was deconvoluted into three peaks corresponding to the functional groups C�O and C−O (532.87 eV) and oxygen in the −SO 3 − group, which is bound to sulfur within the sulfonic acid of the side chain yielding O 1s signal at 532.25 eV. Furthermore, the oxygen in the ether configuration (−F 2 C−O−CF 2 −) is found at 535.45 eV.…”
Section: Sem and Xps Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The study revealed a strong and stable interaction between the sulfonic groups of the Nafion and the carbon black surface, which is probably the result of the fast desolvation of the adsorbed ionomer during the ionization process. This interaction is believed to favor a better coverage of the carbon surface with the polymer chains and leads to a particular arrangement of the Nafion with fluorocarbon backbones oriented toward the outer part of the aggregates …”
Section: Understanding the Properties Of Electrosprayed Catalyst Layersmentioning
confidence: 99%
“…This interaction is believed to favor a better coverage of the carbon surface with the polymer chains and leads to a particular arrangement of the Nafion with fluorocarbon backbones oriented toward the outer part of the aggregates. 49 Electrosprayed catalyst layer properties were further analyzed ex situ for a more complete insight into their unparalleled properties. Mass-transport properties were studied by the hydrogen limiting-current technique and correlated with their water-vapor uptake capability.…”
Section: Understanding the Properties Ofmentioning
confidence: 99%